Investigating The Determining Factors of Tourist Revisit Intention in a Natural-based Tourism Destination - Fatmawati Indah; Olga Frido (E3S Web of Conferences, 2023)
Tourism is one of the growing sectors in Indonesia. Natural-based tourism is one of the most attractive tourism destinations among various tourism types in Indonesia. Investigating factors influencing tourist revisit intention in a natural-based tourism destination is interesting since it could reveal what factors drive tourists to revisit a particular destination they have visited. This study aims to analyze the influence of environmental quality, attractiveness, accessibility, facilities, and tourist satisfaction on tourist objects’ revisit intention. We use a quantitative approach and an explanatory design to test the proposed hypothesis. Respondents in this study were tourists who had visited Sarangan Lake, located in Magetan, East Java. The sampling method uses purposive sampling, and the final usable responses were 168 respondents. The analytical tool used in this research is Structural Equation Modelling (SEM) with the AMOS application program. Results indicated that environmental quality, attractiveness, accessibility, and facilities positively affect tourist satisfaction. Furthermore, tourist satisfaction positively impacts tourist revisit intention. Several research recommendations were discussed in our study.